Quantifying the effect of construction site factors on concrete compressive strength using designed experiments. (2019) - Santamaria, Jorge L.; Valentin, Vanessa; Huerta, Gabriel
Both structured and unstructured factors affect concrete compressive strength. Structured factors, e.g., raw materials, affect concrete production. Unstructured factors, e.g., local conditions, affect concrete quality during the construction phase. The effects of structured factors on concrete metrics are well understood, while there is limited understanding on the effects of unstructured factors. A full 2 5 factorial design was conducted to quantify the effect of five construction site factors including crew experience, compaction method, mixing time, curing humidity and curing temperature. A linear regression model was developed considering significant affecting factors. Model adequacy was evaluated through residual plots. The results indicate that compaction method, mixing time, curing humidity and curing temperature affect concrete compressive strength significantly, with curing temperature having the highest percent contribution (50.0%). The final regression model was used to create a decision-support tool that enables construction workers to find operating conditions and take corrective actions to preserve concrete quality.